In search of homelands: using strontium isotopes to identify biological markers of mobility in late prehistoric Portugal - Waterman, Anna J. (2014)
This study uses strontium isotopes (87Sr/86Sr) in dental enamel from burial populations related to the fortified Chalcolithic settlement site of Zambujal (c. 2800e1800 BC) to distinguish the presence of nonlocal individuals. Zambujal is located in the Estremadura region of Portugal near the Atlantic coast and has long been considered a central location of population aggregation, craft production, and trade during a time of increasing political centralization and social stratification until its eventually abandonment during the Bronze Age. While it is assumed that population migration and long distance trade played an important role in the region’s development, little is known about the migration patterns of individuals or groups. The results of this study find that nine percent (5 out of 55) of the total surveyed individuals can be classified as non-local (based on 87Sr/86Sr values distinct from the local bioavailable range of 0.7090e0.7115 as defined by 2sd of the sampled human mean), the majority of which come from one burial site, Cova da Moura. Comparisons with other regional data suggest the possibility that some of these non-locals come from the Alentejo region of the Portuguese interior, corresponding with known exchange patterns.